Effect of Different Size of Tool Pin Diameter for Butt Joint Between Aluminium and Aluminium by Friction Stir Welding (FSW) - Roslan bin Mohd Dali, Ahmad Syukri bin Roslan; Abu Bakar, Bachik (Progress in Engineering Application and Technology, 2021)
Aluminum alloy finds its applications in various sectors of engineering. This paper discusses the investigation of mechanical properties of butt weld joints of aluminum alloy A1100 having 200 x 75 x 6mm thick sheets each. An experiment was conducted three different tool pin size diameter which is 3mm, 5mm and 7mm, and the rotational speeds used was 990 rpm and traverse speed 27mm/min using conventional milling machine. The experimental results are evaluated by visual inspection and tensile test methods and the defect existing in this process such as poor welded joint surface, flash, lack of penetrations, weld discontinuities, and irregular material flow due to insufficient tool force downwards onto the specimen. The results shows that specimen with diameter tool pin of 3mm obtain the highest peak force of 934.13N, tensile stress 17.49MPa, elongation of 1.89mm which is 6.33%, and yield strength of 13.94MPa. For specimen with diameter tool pin of 5mm, it shows that the peak force is 564.59N, tensile stress 13.03MPa, elongation of 1.48mm which is 5.94% and yield strength of 8.42MPa.